Digital Latin American Poetry: Experimental Language in the Times of Bits - Kozak, Claudia (2019)
The essay examines the role of literature in the digital age -the post-Proustian time of bits-, first by tracing out the history of the digital poem in Argentina and Brazil, and subsequently by discussing two contemporary examples. As a contribution to a dossier on Latin American Digital Literature, the article focuses on several topics such as a succinct definition of digital poetry, the circulation of these digital literary (poetic) texts, the experimental impetus that digital literature entails since the moment it surfaced in the 1950s and the freedom this kind of literature might have to resist and to flow over transversal and alternative paths, even from within the digitization of daily contemporary life that drives more or less hegemonic and standardized social forms.